Ethiopian-Somali Conflict 1977—1978: According to US Central Intelligence Agency - R. R. Tukhvatullin; U. N. Kudashev (Научный диалог, 2023)
The analysis by the US Central Intelligence Agency of the military and political aspects of the Ogaden War (1977—1978) is considered. On the basis of declassified and published documents, the main issues related to the Somali-Ethiopian conflict that worried the CIA are revealed. It establishes the degree of awareness of the Office about certain events related to the war in the Ogaden, and also determines how successful the forecasts made during the conflict were. With the involvement of domestic, American, Ethiopian and Somali historiography, it is shown that the CIA, despite the lack of information, established certain facts quite accurately, but regularly made mistakes in their judgments about further events. The forecasts of the Office regarding a possible conflict between Ethiopia and Somalia in January — July 1977, which turned out to be correct only in small things or in obvious facts, are highlighted. It is shown that the CIA correctly identified the conflict potential in the region, but did not determine exactly where the war would begin. Regarding the role of the CIA in covering the fighting in the Ogaden in July 1977 — March 1978 it is noted that the Office was successful in identifying short-term trends, but did not establish long-term ones.